2022
DOI: 10.1097/bot.0000000000002437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Length Stability on Complications in the Treatment of Preadolescent Diaphyseal Femur Fractures Treated With Elastic Stable Intramedullary Nailing

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The current study by Nixon and his St Louis coauthors 8 in this issue of J Orthop Trauma adds to the growing body of literature (at least the seventh study) that supports the use of ESIN in unstable femoral shaft fractures. 9–14 Using the same definition of unstable as Sink et al did in 2005, Nixon et al compared 63 stable and 43 unstable femoral shaft fracture patients and found no difference in major complication rates (12.7% and 11.6%, respectively).…”
mentioning
confidence: 63%
“…The current study by Nixon and his St Louis coauthors 8 in this issue of J Orthop Trauma adds to the growing body of literature (at least the seventh study) that supports the use of ESIN in unstable femoral shaft fractures. 9–14 Using the same definition of unstable as Sink et al did in 2005, Nixon et al compared 63 stable and 43 unstable femoral shaft fracture patients and found no difference in major complication rates (12.7% and 11.6%, respectively).…”
mentioning
confidence: 63%
“…All cases were identified within 2 years of the injury, and the risk of growth disturbance peaked at the age of 9.1 years for girls, the age of 10.2 years for boys, and initial treatment at an outside facility. In a separate study, children <10 years of age did not experience increased complications after flexible nailing of lengthunstable femoral fractures and were not at risk for more complications, early shortening, or leg-length inequality compared with length-stable femoral fractures 11 . if the CRP did not reduce by 50% by days 4 and 5 and the patient required a surgical procedure, this predicted chronic complications from the osteomyelitis.…”
Section: Lower-extremity Injuriesmentioning
confidence: 87%
“…Available Evidence for Flexible Intramedullary Nails in Length-Unstable Fractures Consequently, there have been recent attempts by certain authors to debunk the notion that "lengthunstable" (according to Sink et al) fractures are rarely amenable to FIN. 9,[14][15][16][17] The selection bias associated with retrospective data collected after 2005 is a major limiting factor of these studies. Bearing that in mind, these recent authors collectively suggest that minimally unstable patterns in otherwise appropriate patients (age, weight, fracture location) may be appropriate for FIN at the discretion of an experienced pediatric orthopaedic surgeon.…”
Section: Figurementioning
confidence: 99%
“…They defined Winquist 0 to 2 comminution as length-stable, and all fractures had some form of postoperative immobilization. Nixon et al 17 claimed length-unstable femur fractures are not at increased risk of complications after FIN. However, they excluded very proximal or distal fractures (within 3 cm of the lesser trochanter or 5 cm of the distal femoral physis) and understandably categorized Winquist 1 comminution as length-stable.…”
Section: Flexible Intramedullary Nailsmentioning
confidence: 99%